Biogenic ZnO nanoparticles: structural characterisation and bioactivity evaluation - Abhimanyu Parasram Pawar; Kishor Sudhir Naktode; Arvind Janardhan Mungole; Srinivas Anga (Chemistry Journal of Moldova: General, Industrial and Ecological Chemistry)

(untitled)
Zinc oxide nanoparticles were synthesized via a green route using Nicotiana plumbaginifolia plant extract, serving as a novel bio-reducing and stabilizing agent. Structural analysis through X-ray diffraction confirmed the hexagonal wurtzite crystalline structure, while Fourier-transform infrared spectroscopy and energy-dispersive X-ray spectroscopy affirmed the presence of Zn-O bonds and high purity. Morphological characterization by scanning electron microscopy and transmission electron microscopy revealed spherical nanoparticles with sizes ranging from 16 to 24 nm. The calculated optical band gap was 3.33 eV. A prominent FTIR peak at 480 cm⁻¹ indicated Zn-O stretching vibrations. The Zinc oxide nanoparticles exhibited significant antibacterial activity against Pseudomonas aeruginosa (18 mm), Escherichia coli (19 mm), Klebsiella pneumoniae (19 mm), and Staphylococcus aureus (18 mm) at 100 μL, as evaluated by the well diffusion method. Additionally, the nanoparticles showed strong antioxidant activity, achieving 75.59% DPPH radical scavenging at 250 μg/mL, indicating potential biomedical applications.